Socioeconomic profile of sheep farmers and environmental aspects of beef sheep farming in the Santarém and Mojuí dos Campos municipalities of Pará state, Brazil - Queiroz, Angela Cira Lima; Coêlho, Tássio Alves; Chagas-de-Souza, Darlison; da Silva, Alanna do Socorro Lima (Revista Sítio Novo, 2024)
In this study, we aimed to describe the socioeconomic profile of sheep farmers and the environmental aspects involving the raising of beef sheep in the municipalities of Santarém and Mojuí dos Campos, Pará State, Brazil. This research was carried out by means of an in loco interview, which collected data from 21 sheep farmers. Here, we present for the first time the overview of the breeding system in these municipalities, the data revealed that 90.47% of the breeders were men, most have a complete college education, none of the producers participate in social programs and end up raising sheep by family influence. Even so, more than 60% of the breeders use beef sheep farming as their main source of income. The system most used on the properties was the semi-extensive system, with feed supplementation offered in troughs. An important fact is that only three properties end up using permanent protection areas in the production system. The biggest costs associated are in feed supplementation and diseases, It is notorious for the lack of technical support from entities that promote production, improvement and guidance about the production of supplementary feeding on the property.